IMPLEMENTASI PELAPORAN PROGRAM CEK KESEHATAN GRATIS APLIKASI SATU SEHAT INDONESIAKU (SSI) - Yovita Magdalena Panjaitan; Betty Sirait; Venny Mayumi Gultom (LPPM STIKes Mitra Adiguna, 2026)
In order to improve public health, the government is organizing a Free Health Check Program as part of its preventive and promotive health services. The purpose of this study is to determine the implementation of reporting the Satu Sehat Indonesiaku (SSI) application's free health check program to support the optimization of program record-keeping and reporting. Qualitative research with a cross-sectional design. The population is all the officers in the research area. The samples used were taken using the purposive sampling technique, which involved 4 informants with predetermined inclusion criteria. The research results indicate that the implementation of the Satu Sehat Indonesiaku (SSI) application at the Ogan Permata Indah (OPI) Community Health Center is running well and contributes positively to the effectiveness and efficiency of recording and reporting free health check-up activities (CKG). The SSI application simplifies data processing, reduces input errors, and supports integrated and timely reporting. Most officers have a positive perception of using the SSI application. However, limitations in internet connectivity, differences in staff technical skills, and the need to improve the application's interface for better user-friendliness were still encountered. It is recommended to enhance staff capacity thru training and technical assistance, along with strengthening internet connectivity and refining the features of the Satu Sehat Indonesiaku (SSI) application. Additionally, regular monitoring and evaluation are needed to maintain the effectiveness of reporting.